The Validity of Physiological Measures to Identify Differences in Intrinsic Cognitive Load - Ayres, Paul; Lee, Joy Yeonjoo; Paas, Fred; van Merriënboer, Jeroen J. G. (Frontiers in Psychology, 2021)
A sample of 33 experiments was extracted from the Web-of-Science database over a 5-year period (2016-2020) that used physiological measures to measure intrinsic cognitive load. Only studies that required participants to solve tasks of varying complexities using a within-subjects design were included. The sample identified a number of different physiological measures obtained by recording signals from 4 main body categories (heart & lungs, eyes, skin, and brain), as well as subjective measures. The overall validity of the measures was assessed by examining construct validity and sensitivity. It was found that the vast majority of physiological measures had some level of validity, but varied considerably in sensitivity to detect subtle changes in intrinsic cognitive load. Validity was also influenced by the type of task. Eye-measures were found to be the most sensitive followed by the heart & lungs, skin, and brain. However, subjective measures had the highest levels of validity. It was concluded that a combination of physiological and subjective measures was most effective in detecting changes in intrinsic cognitive load.